Leibniz algebras, having a dense family of ideals - Semko, N.N.; Skaskiv, L.V.; Yarovaya, O.A. (Carpathian Mathematical Publications, 2020)
We say that a Leibniz algebra L has a dense family of ideals, if for every pair of subalgebras A, B of L such that AB and A is not maximal in B there exists an ideal S such that ASB. We study the Leibniz algebras, having a dense family of ideals.